Overlooked seasonal groundwater nutrient fluxes rival anthropogenic point sources across a variable land‐use tidal river - James A. Padilla‐Montalvo; Douglas R. Tait; Michael J. Reading; Benjamin T. Stewart; Angus Ferguson; Iremar Fernandez‐Vazquez; James Z. Sippo; Shivanesh Rao; Mitch Call; Christopher Ralph; Josh Guyat; Jenny Rogers; et al. (Limnology and Oceanography, 2025)
Understanding groundwater–surface water connectivity in tidal freshwater zones is essential for managing ecosystems within the riverine–estuarine continuum. Groundwater discharge is a key source of dissolved nutrient loads that can lead to eutrophication, deoxygenation, and other ecosystem imbalances in coastal environments. However, groundwater is an often‐overlooked nutrient delivery pathway, with limited studies quantifying groundwater inputs into freshwater transitional zones. Here, we quantify groundwater discharge and its associated nutrient fluxes along a ≈ 75 km section of a tidal freshwater zone within the Hawkesbury–Nepean River (New South Wales, Australia), which is surrounded by multiple land uses. High‐resolution timeseries and spatial surveys were employed over three hydrologically distinct seasons using the naturally occurring radioisotope tracer, radon. Survey results revealed decreasing surface water radon activity and nutrients toward the downstream estuarine boundary. Estimated groundwater discharge rates were highest in the upstream reaches (6.0–12.5 cm d −1 ), regardless of seasonal hydrological dynamics, and decreased downstream, aligning with a reduction in irrigation‐dependent agricultural practices and a change in adjacent catchment morphology. During the dry period, groundwater accounted for up to ≈ 68% of upstream river inputs. Groundwater discharge was also a major source of dissolved inorganic nitrogen, contributing between 0.8 and 1.1 times the inputs from local wastewater treatment plants, and up to 15 times more phosphate than upstream river sources. These findings highlight the role of groundwater discharge as a nutrient driver for tidal freshwater zones, which could have significant implications for future management strategies in these environments.